A tunable multicolour `rainbow' filter for improved stress and dislocation density field mapping in polycrystals using X‐ray Laue microdiffraction. (6th February 2013) - Robach, Odile; Micha, Jean‐Sébastien; Ulrich, Olivier; Geaymond, Olivier; Sicardy, Olivier; Härtwig, Jürgen; Rieutord, François
<x xml:space="preserve">Abstract</x> White‐beam X‐ray Laue microdiffraction allows fast mapping of crystal orientation and strain fields in polycrystals, with a submicron spatial resolution in two dimensions. In the well crystallized parts of the grains, the analysis of Laue‐spot positions provides the local deviatoric strain tensor. The hydrostatic part of the strain tensor may also be obtained, at the cost of a longer measuring time, by measuring the energy profiles of the Laue spots using a variable‐energy monochromatic beam. A new `rainbow' method is presented, which allows measurement of the energy profiles of the Laue spots while remaining in the white‐beam mode. It offers mostly the same information as the latter monochromatic method, but with two advantages: (i) the simultaneous measurement of the energy profiles and the Laue pattern; (ii) rapid access to energy profiles of a larger number of spots, for equivalent scans on the angle of the optical element. The method proceeds in the opposite way compared to a monochromator‐based method, by simultaneously removing several sharp energy bands from the incident beam, instead of selecting a single one. It uses a diamond single crystal placed upstream of the sample. Each Laue diffraction by diamond lattice planes attenuates the corresponding energy in the incident spectrum. By rotating the crystal, the filtered‐out energies can be varied in a controlled manner, allowing one to determine the extinction energies of several Laue spots of the studied sample. The energies filtered out by the diamond crystal are obtained by measuring its Laue pattern with another two‐dimensional detector, at each rotation step. This article demonstrates the feasibility of the method and its validation through the measurement of a known lattice parameter.